Structural and functional characterization of the histidine phosphatase domains of human Sts-1 and Sts-2() - Zhou, Weijie (Biochemistry, 2017)
The suppressor of T-cell signaling (Sts) proteins, Sts-1 and Sts-2, are homologous phosphatases that negatively regulate signaling pathways downstream of the T-cell receptor. Functional inactivation of Sts-1 and Sts-2 in a murine model leads to resistance to systemic infection by the opportunistic pathogen, C. albicans. This suggests that modulation of the host immune response by inhibiting Sts function may be a viable strategy to treat these deadly fungal pathogen infections. To better understand the molecular determinants of function and structure, we characterized the structure and steady-state kinetics of the histidine phosphatase domains of human Sts-1 (Sts-1(HP)) and Sts-2 (Sts-2(HP)). We solved the X-ray crystal structures of Sts-1(HP), unliganded and in complex with sulfate to 2.5 Å and 1.9 Å, respectively, and the structure of Sts-2(HP) with sulfate to 2.4 Å. The steady-state kinetic analysis shows, as expected, that Sts-1(HP) has a significantly higher phosphatase activity than that of Sts-2(HP), and that the human and mouse proteins behave similarly. In addition, comparison of the phosphatase activity of full-length Sts-1 protein to Sts-1(HP) reveals similar kinetics, indicating that Sts-1(HP) is a functional surrogate for the native protein. We also tested known phosphatase inhibitors and identified that the SHP-1 inhibitor, PHPS1, is a potent inhibitor of Sts-1 (K(i) of 1.05 ± 0.15 μM). Finally, we demonstrated that human Sts-1 has robust phosphatase activity against the substrate, Zap-70, in a cell-based assay. Collectively, these data suggest that the human Sts proteins are druggable targets and provides a structural basis for future drug development efforts.